Perspective paper: intellectual capital, knowledge management, politics and billionaires. (19th July 2019) - Tomé, Eduardo
We analyse if intellectual capital can have an impact in political terms namely in what comes to influence the outcome of elections. We base our analysis in usual and well-known concepts and theories about intellectual capital which has been widely used in relation with companies, organisations, and regions, and that in this paper we extend to apply to billionaires in the context of political power. We find that both conceptually and in practice intellectual capital seems to have a major impact in the political process and in the political results, particularly when it is the case of billionaires. Intellectual capital generates billionaires and is also a major enabler of the political success of billionaires. However, and quite decisively, intellectual capital only becomes decisive if billionaires are good at political knowledge management. Finally, this influence in elections is itself a mirror of the growing influence of intellectual capital in societies.